2017
DOI: 10.1063/1.4975492
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial growth and characterization of Bi1-xSbx spin Hall thin films on GaAs(111)A substrates

Abstract: We grew and characterized Bi1-xSbx thin films on GaAs(111)A substrates by molecular beam epitaxy. By optimizing the growth condition, we were able to grow Bi1-xSbx thin films epitaxially with the Sb concentration ranging from 0% to 100% and the epitaxial orientation of Bi1-xSbx(001)//GaAs(111). The conductivity of Bi1-xSbx exceeds 105 Ω−1 m−1 and approaches those of bulk values for thick enough thin films, which are higher than those of other Bi-based topological insulators by at least an order of magnitude. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 26 publications
1
48
0
1
Order By: Relevance
“…It has been reported that a band gap opens up in thin films of Bi 0.74 Sb 0.26 due to quantum confinement effects. Therefore Bi 0.74 Sb 0.26 films may show topological insulating behavior [41].…”
Section: Figmentioning
confidence: 99%
“…It has been reported that a band gap opens up in thin films of Bi 0.74 Sb 0.26 due to quantum confinement effects. Therefore Bi 0.74 Sb 0.26 films may show topological insulating behavior [41].…”
Section: Figmentioning
confidence: 99%
“…However, a large lattice mismatch sometimes does not induce a strain on 2D materials. For instance, 2D BiSb can be grown on GaAs(111) or MnGa substrate without strain effect despite the large lattice mismatch between them . Nevertheless, the substrate still contributes a lot in the system.…”
Section: Theoretical Design Of 2d V‐v Binary Materialsmentioning
confidence: 99%
“…In 2017, Hai et al reported the MBE growth of high‐quality β‐BiSb nanosheets on GaAs(111) substrates . Through optimizing the growth conditions, the Sb concentration can be modified from 0 to 1.…”
Section: Realizing 2d V‐v Binary Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The electronic structure of Bi and Sb has been measured in several experiments by angle-resolved photoemission spectroscopy (ARPES) [7][8][9][10][11][12][13][14][15]. The first-ever three dimensional topological insulator (TI) has been realized in the Bi 1−x Sb x alloy [16][17][18][19][20][21][22]. Both Bi and Sb are semimetals with a negative band gap which separates the conduction and valence bands everywhere in the Brillouin zone.…”
Section: Introductionmentioning
confidence: 99%